2009
DOI: 10.1097/dad.0b013e3181914cf1
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Solitary Neural Hamartoma: Report of an Unusual Case

Abstract: Cutaneous hamartomas are tumor-like proliferations of tissue indigenous to the organ but arranged abnormally. There are examples in the literature of cutaneous hamartomas composed of a variety of different components. To our knowledge, there is no previous report of such cutaneous solitary neural hamartoma. Our case occurred in a 51-year-old man with pain and paresthesia in the right shoulder associated with a nodule that was surgically removed. There was no history of trauma, other skin nodules, neurofibromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Cutaneous solitary neural hamartoma is described as an unencapsulated nodule of haphazardly arranged, thick nerve fascicles in a periadnexal distribution, within the papillary and reticular dermis. These thick nerve bundles are S100 positive, contain neurofilament‐positive axons and are surrounded by EMA‐positive perineurium . Unlike the nerve fascicles in cutaneous solitary neural hamartoma, the fibers in our series were smaller, vertically oriented, mostly confined to the papillary dermis and lacked a periadnexal distribution.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Cutaneous solitary neural hamartoma is described as an unencapsulated nodule of haphazardly arranged, thick nerve fascicles in a periadnexal distribution, within the papillary and reticular dermis. These thick nerve bundles are S100 positive, contain neurofilament‐positive axons and are surrounded by EMA‐positive perineurium . Unlike the nerve fascicles in cutaneous solitary neural hamartoma, the fibers in our series were smaller, vertically oriented, mostly confined to the papillary dermis and lacked a periadnexal distribution.…”
Section: Discussionmentioning
confidence: 63%
“…Although most dermal lesions with neural differentiation are classifiable using well‐established diagnoses, some are not. As a consequence, several new entities have been reported in the last decade …”
Section: Introductionmentioning
confidence: 99%
“…Prior to that, Goldsmith et al 6 described a case of leiomyomatous hamartoma of the posterior tongue leading to dysphagia in a 16-year-old, whereas Miyamoto et al 7 documented a lingual hamartoma in a child with a cleft palate. Al Habeeb et al 8 reported a solitary but cutaneous neural hamartoma in a middle-aged individual. The lesion had histological characteristics comprising of numerous mature nerve bundles within the papillary dermis.…”
Section: Discussionmentioning
confidence: 99%
“…Al Habeeb et al have described a case of cutaneous solitary neural hamartoma in a 51-year-old man [1]. This right shoulder unencapsulated lesion was composed of mature nerve bundles abnormally high within the papillary dermis, extending into the reticular dermis with a periadnexal distribution.…”
Section: Discussionmentioning
confidence: 99%